Streptomyces and their specialised metabolites for phytopathogen control – comparative in vitro and in planta metabolic approaches - Dow, Lachlan; Gallart, Marta; Ramarajan, Margaret; Law, Simon R.; Thatcher, Louise F. (Frontiers in Plant Science, 2023)
In the search for new crop protection microbial biocontrol agents, isolates from the genus Streptomyces are commonly found with promising attributes. Streptomyces are natural soil dwellers and have evolved as plant symbionts producing specialised metabolites with antibiotic and antifungal activities. Streptomyces biocontrol strains can effectively supress plant pathogens via direct antimicrobial activity, but also induce plant resistance through indirect biosynthetic pathways. The investigation of factors stimulating the production and release of Streptomyces bioactive compounds is commonly conducted in vitro, between Streptomyces sp. and a plant pathogen. However, recent research is starting to shed light on the behaviour of these biocontrol agents in planta, where the biotic and abiotic conditions share little similarity to those of controlled laboratory conditions. With a focus on specialised metabolites, this review details (i) the various methods by which Streptomyces biocontrol agents employ specialised metabolites as an additional line of defence against plant pathogens, (ii) the signals shared in the tripartite system of plant, pathogen and biocontrol agent, and (iii) an outlook on new approaches to expedite the identification and ecological understanding of these metabolites under a crop protection lens.